2016
DOI: 10.1128/jcm.02850-15
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of a Fully Automated Multiplex PCR Panel for Detection of Central Nervous System Pathogens

Abstract: We evaluated a multiplexed PCR panel for the detection of 16 bacterial, viral, and fungal pathogens in cerebrospinal fluid. Panel results were compared to routine testing, and discrepancies were resolved by additional nucleic acid amplification tests or sequencing. Overall, the positive and negative agreements across methods were 92.9% and 91.9%, respectively. A cute meningoencephalitis (ME) is an inflammatory disease of the central nervous system (CNS) that can result in significant morbidity and mortality. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
51
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 14 publications
7
51
6
Order By: Relevance
“…The study by Leber and colleagues represents the largest clinical assessment of a molecular panel designed to aid in the diagnosis of meningoencephalitis. This study, combined with previous retrospective reports, suggest that ME panel test characteristics are acceptable for clinical care (2,3,7). The main benefit of the ME panel is the potential for more rapid results, which could help inform optimal therapy and resource utilization.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The study by Leber and colleagues represents the largest clinical assessment of a molecular panel designed to aid in the diagnosis of meningoencephalitis. This study, combined with previous retrospective reports, suggest that ME panel test characteristics are acceptable for clinical care (2,3,7). The main benefit of the ME panel is the potential for more rapid results, which could help inform optimal therapy and resource utilization.…”
mentioning
confidence: 74%
“…Most of the viral targets showed excellent agreement with comparator PCRs, even though the multiplex format is slightly less sensitive than the comparator singleplex tests. A notable exception was the calculated sensitivity of the HHV-6 target (86%) and, in a previous report, the cytomegalovirus (CMV) target (57%) (3). Although the ME panel missed two enteroviral infec-tions, the majority of these infections were detected (44/46; sensitivity, 96%).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…There were significant discrepancies between the panel and cryptococcal antigen results, with correlation in only 57% (6/14) of the cryptococcal antigen-positive specimens. Of note, no culture results were available and confirmatory testing by sequencing was also negative (11). Because of the rarity of the infection, L. monocytogenes was not detected in either study; importantly, there were also no false-positive cases identified (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar puncture revealed leucocytes 5 × 10 6 /L but no other abnormalities. Cerebrospinal fluid multiplex polymerase chain reaction (PCR) was negative for common bacterial and viral pathogens and specific PCR for herpes simplex viruses 1 and 2, varicella and enterovirus were negative. Serological testing for melioidosis, mycoplasma, hepatitis B and C and human immunodeficiency virus were all negative.…”
mentioning
confidence: 99%